1997
DOI: 10.1074/jbc.272.26.16301
|View full text |Cite
|
Sign up to set email alerts
|

Individual Residues Contribute to Multiple Differences in Ligand Recognition between Vesicular Monoamine Transporters 1 and 2

Abstract: Molecular cloning has identified two vesicular monoamine transporters (VMATs), one expressed in non-neural cells of the periphery (VMAT1) and the other by multiple monoamine cell populations in the brain (VMAT2). Functional analysis has previously shown that VMAT2 has a higher affinity than VMAT1 for monoamine neurotransmitters as well as the inhibitor tetrabenazine. The analysis of chimeric transporters has also identified two major regions required for the high affinity interactions of VMAT2 with these ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 25 publications
1
41
1
Order By: Relevance
“…Cys-431 has been identified in human VMAT2 as a residue that confers sensitivity to thiolreactive reagents, but the reaction is prevented by TBZ (27). Mutations in Tyr-434 reduce the affinity to serotonin and TBZ (28,29). In TM2, Lys-139 has been identified as part of a charge pair with Asp-427 (24).…”
Section: Discussionmentioning
confidence: 99%
“…Cys-431 has been identified in human VMAT2 as a residue that confers sensitivity to thiolreactive reagents, but the reaction is prevented by TBZ (27). Mutations in Tyr-434 reduce the affinity to serotonin and TBZ (28,29). In TM2, Lys-139 has been identified as part of a charge pair with Asp-427 (24).…”
Section: Discussionmentioning
confidence: 99%
“…cDNAs were cloned into pcDNA1/Amp (Invitrogen, Carlsbad, CA). To facilitate the subcloning of VMAT2 mutants, we used a cDNA with two silent mutations that create a BglII and a SalI site at nucleotides 440 and 1302, respectively (34). A sequence encoding the hemaglutinin epitope, YPYDVPDYA, was inserted after the codon for glycine 96 in the VMAT2 cDNA (35) and after the codon for glycine 105 in the VAChT cDNA (28).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, using immunoprecipitation as another technique, we established that the nitration of tyrosine residues via VMAT2 was caused by rotenone and the reduced dopamine uptake activity of VMAT2. A previous study demonstrated that tyrosine 434 of VMAT2 plays an important role in dopamine affinity and the activity of dopamine transport (Finn and Edwards, 1997). The replacement of tyrosine 434 with alanine increases the affinity of VMAT2 for dopamine and reduces the rate of dopamine transport.…”
Section: Nitration Signal Inhibits and Redistributes Vmat2 937mentioning
confidence: 99%